Effects of pigeon pea and plantain starches on the compressional, mechanical and disintegration properties of paracetamol tablets (2006)
A study has been made of the effects of pigeon pea starch obtained from the plant Cajanus cajan (L) Millisp. (family Fabaceae) and plantain starch obtained from the unripe fruit of Musa paradisiaca L. (family Musaceae) on the compressional, mechanical, and disintegration properties of paracetamol tablets in comparison with official corn starch BP. Analysis of compressional properties was done by using density measurements, and the Heckel and Kawakita equations, whereas the mechanical properties of the tablets were evaluated by using tensile strength (T-a measure of bond strength) and brittle fracture index (BFI-a measure of lamination tendency). The ranking for the mean yield pressure, Py, for the formulations containing the different starches was generally corn < pigeon pea < plantain starch while the ranking for Pk, an inverse measure of the amount of plasticity, was pigeon pea < plantain < corn starch, which indicated that formulations containing corn starch generally exhibited the fastest onset of plastic deformation, whereas those formulations containing pigeon pea starch exhibited the highest amount of plastic deformation during tableting. The tensile strength of the tablets increased with increase in concentration of the starches while the Brittle Fracture Index decreased. The ranking for T was pigeon pea > plantain > corn starch while the ranking for BFI was corn > plantain > pigeon pea starch. The bonding capacity of the formulations was in general agreement with the tensile strength results. The disintegration time (DT) of the formulation increased with concentration of plantain and corn starches but decreased with concentration of pigeon pea starch. The general ranking of DT values was plantain < pigeon pea < corn starch. Notably, formulations containing pigeon pea starch exhibited the highest bond strength and lowest brittleness, suggesting the usefulness of pigeon pea starch in producing strong tablets with minimal lamination tendency. Plantain starch, on the other hand, would be more useful where faster disintegration of tablet is desired. The results show that the starches could be useful in various formulations depending on the intended use of the tablets with the implication that the experimental starches can be developed for commercial purposes